L-Carnitine Tartrate Downregulates the ACE2 Receptor and Limits SARS-CoV-2 Infection - Bellamine, Aouatef; Pham, Tram N. Q.; Jain, Jaspreet; Wilson, Jacob; Şahin, Kazım; Dallaire, Frederic; Cohen, Eric A. (Mdpi, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been responsible for one of the worst pandemics in modern history. Several prevention and treatment strategies have been designed and evaluated in recent months either through the repurposing of existing treatments or the development of new drugs and vaccines. In this study, we show that L-carnitine tartrate supplementation in humans and rodents led to significant decreases of key host dependency factors, notably angiotensin-converting enzyme 2 (ACE2), transmembrane protease serine 2 (TMPRSS2), and Furin, which are responsible for viral attachment, viral spike S-protein cleavage, and priming for viral fusion and entry. Interestingly, pre-treatment of Calu-3, human lung epithelial cells, with L-carnitine tartrate led to a significant and dose-dependent inhibition of the infection by SARS-CoV-2. Infection inhibition coincided with a significant decrease in ACE2 mRNA expression levels. These data suggest that L-carnitine tartrate should be tested with appropriate trials in humans for the possibility to limit SARS-CoV-2 infection.
Keywords: L-carnitine; SARS-CoV-2; COVID-19; exercise; inflammation; ACE-2; Furin; TMPRSS2